Evaluación del potencial fitorremediador de la especie dieffenbachia seguine (jacq.) Schott en suelos contaminados por mercurio, en el sector de san antonio, parroquia guadalupe, perteneciente al cantón Zamora, provincia de Zamora Chinchipe - Paqui Maza, Richard Bladimir (2016)
The objective of this research project was to evaluate the phytoremediation potential of the plant species Dieffenbachia seguine (Jacq.) Schott, in soils contaminated by mercury, generated by mining activity in the San Antonio neighborhood of Guadalupe, Zamora town, in The present research set out two specific objectives: To determine the degree of current contamination of the soil by mercury and to evaluate the phytoremediation potential of the species Dieffenbachia seguine (Jacq.) Schott. In the area where there has been gold extraction, extracted the amount of 0.364 m3 of soil for the establishment of four trays, followed by planting of 8 plants in each platabanda giving a total of 21 plants, which were given the respective monitoring for four months. The initial laboratory results determined in treatment 1,the soil is contaminated with an average of 63,66 mg/kg of mercury, while sample witness present a value of 82mg/kg exceeding the permissible maximum limit which sets the 028 Ministerial Agreement. After the process of phytoremediation is determined that the amount of mercury in the treatment 1 decreased to a concentration average of 9.01 mg / kg of mercury, while it shows witness to a value of 11.0 mg / kg, these values exceed limits the maximum permissible of the agreement Ministerial 028. The efficiency of the treatment of the vegetal species Dieffenbachia seguine is 85,83%, however the witness in 86.59% decreased its concentration of mercury in the soil.